BIEDNY MICKIEWICZ - Fiłosofow, Dymitr; Skalińska, Ewangelina (Colloquia Litteraria, 2019)
“Poor Mickiewicz” The journalistic paper by Dmitri Filosofov presented here was written during his long stay in Poland. It clearly shows ways in which this brilliant editor and a ‘political thinker’ referred to literary texts crucial for Poles, their culture and self-awareness. In this paper he dealt with stereotypical ways in which Mickiewicz’s poem “Do Przyjaciół Moskali” (“To Our Rus- sian Friends”) was treated in this period. Filosofov, returned to the poem’s primordial meaning and asked questions, still valid today, about possibilities of Polish-Russian dialogue, but he also warned his readers that a dialogue with Bolshevik authorities would never be identical with a dialogue with Russians of anti-Bolshevik social, cultural and political views.